Wspólna Polityka Rolna i jej kapitał instytucjonalny w ocenie użytkowników towarowych gospodarstw rolnych regionu opolskiego = CAP and its institutional capital as estimated by the users of the marchandise agricultural households in Opole region - Sokołowska, Stanisława; Bisaga, Anna (PAN IGiPZ, 2016)
After 10 years of Poland’s accession to the EU, the CAP instruments have strengthen the development of merchandise agricultural households, adjusted them for managing environmental functions and have initiated the process of adapting to the knowledge based economy. The paper attempts to determine the impact of CAP and its institutional environment on the development of merchandise agricultural households in Opole region. The study was conducted with the method of questionnaire interview addressed to supervisors of the above mentioned households located in the representative agricultural areas of Opole region. Based on the research conducted in 2008 and 2014 it has been stated that further transformation processes concerning rural areas will depend on the “implantation” in the social networks of farmers in the existing, implemented institutional environment and on the estimation of impact they exert on changes in agricultural households on different levels of their functioning.
Keywords: sustainable development; territory; institutional environment of Common Agricultural Policy; modernization of farms